2003
DOI: 10.1089/088282403322017857
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus and Asthma

Abstract: Rhinoviruses (RVs) cause the majority of common colds, which often provoke wheezing in patients with asthma. The precise mechanisms responsible for the RV infection-induced exacerbations of bronchial asthma are still uncertain. However, several reports reveal airway hyperresponsiveness, increases in chemical mediators in airway secretions such as kinin and histamine, and airway inflammation in patients with bronchial asthma after RV infection. RV infection induces an accumulation of inflammatory cells in airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 70 publications
0
26
0
1
Order By: Relevance
“…Maximum production of ICAM-1 occurs 18 to 24 h after cytokine stimulation [8]. Ligands for ICAM-1 include CD11/CD18 receptors [26,29,30], fibrinogen [31], rhinovirus receptors [32] and plasmodium falciparum [33].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum production of ICAM-1 occurs 18 to 24 h after cytokine stimulation [8]. Ligands for ICAM-1 include CD11/CD18 receptors [26,29,30], fibrinogen [31], rhinovirus receptors [32] and plasmodium falciparum [33].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Papadopoulos et al 10 found local induction of proinflammatory mediators that could provide a mechanism to explain how lower airway infection can lead to inflammation and asthma. RV infection resulted in an increase in mRNA expression and subsequent translation of IL-6, IL-8, and IL-16.…”
Section: How Does Rv Modulate Inflammatory Mediators Of Epithelial Cementioning
confidence: 99%
“…Low-dose and long-term therapy with erythromycin, which reduces ICAM-1 expression in the airway epithelial cells and inhibits rhinovirus infection, is effective for chronic obstructive pulmonary disease, diffuse panbronchiolitis and chronic sinusitis [14][15][16][17]. It has also been reported that macrolides reduce the progression of bleomycin-induced lung injury in mice by inhibiting the induction of adhesion molecules, and neutrophil and macrophage migration into the airspace [18,19].…”
Section: Introductionmentioning
confidence: 99%